2018
DOI: 10.33546/bnj.313
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Barriers to Hypertension Management in Minangkabau Ethnic Group in Payakumbuh Indonesia: A Phenomenological Study

Abstract: Background: Understanding barriers to hypertension managements remains important to reduce the hypertension rate in community. Minangkabau is one of the ethnic groups in West Sumatra Indonesia that has a high proportion of people with hypertension although its management has been implemented.Objective: This study aims to explore the experiences of barriers to hypertension management in Minangkabau ethnic group in Payakumbuh, Indonesia.Methods: This was a phenomenological study with twelve respondents selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Having hypertension focuses on salty food, changing the meaning of experiences related to food/eating. This is similar to another part of Indonesia, at Minangkabau Payakumbuh, where people like to eat salty and high-fat food; thus, it serves as a barrier to managing hypertension (Kurnia et al, 2018). Also, in a study in Bangladesh, the patients with hypertension were aware that they should restrict salt intake, but most failed to practice it (Jahan et al, 2020).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Having hypertension focuses on salty food, changing the meaning of experiences related to food/eating. This is similar to another part of Indonesia, at Minangkabau Payakumbuh, where people like to eat salty and high-fat food; thus, it serves as a barrier to managing hypertension (Kurnia et al, 2018). Also, in a study in Bangladesh, the patients with hypertension were aware that they should restrict salt intake, but most failed to practice it (Jahan et al, 2020).…”
Section: Discussionmentioning
confidence: 75%
“…Hypertension is often called a silent killer condition without obvious symptoms in its early stages, which influences the lives of patients (Franklin et al, 2017) and causes comorbidities such as cerebrovascular disease, heart failure, and chronic renal failure (Hakim & Bagheri, 2014;Kurnia et al, 2018). In addition, hypertension also has an effect on psychological aspects, such as anxiety and depression (Shamsi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For study settings, in quantitative and mixed-method studies, 10 studies took place nationally, 24 , 41 , 47–51 , 53 , 63 , 64 19 in the urban areas, 20 , 21 , 23 , 31–33 , 36–38 , 40 , 42 , 44–46 , 52 , 54 , 55 , 58 , 76 16 in rural areas, 22 , 25–29 , 34 , 39 , 43 , 56 , 57 , 59–62 , 75 and two studies in multiple settings. 30 , 35 For quantitative studies, four of them were conducted in urban settings, 66 , 67 , 70 , 71 five were in the rural area 65 , 69 , 72–74 and one study could not be specified. 68 Overall, thirteen 22 , 26–29 , 32 , 42 , 45 , 57–60 , 64 studies have the mean age of older people as the participants (60 years old and above), whereas the rest of the studies were adults 18 years and older.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the quantitative and mixed-method studies, body weight management (29 studies 20 , 24 , 25 , 29 , 30 , 33 , 36 , 39–50 , 52 , 53 , 56–62 , 64 ) and physical exercise (22 studies 21 , 22 , 24 , 30–33 , 35 , 38 , 40–43 , 45 , 47 , 52 , 53 , 56 , 57 , 60 , 61 , 75 ) were the most reported, whereas in the qualitative studies, medication adherence and diet intake was the most reported self-care practice. In addition, a few studies described alternative self-care management methods such as stress-relieving methods (6 studies 35 , 40 , 60 , 66 , 68 , 75 ), sleep and rest (2 studies 68 , 74 ), and spiritual fulfilment was described in one study.…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
See 1 more Smart Citation